Quantifying brain volumes for Multiple Sclerosis patients follow‐up in clinical practice – comparison of 1.5 and 3 Tesla magnetic resonance imaging. Issue 2 (12th January 2016) - Lysandropoulos, Andreas P.; Absil, Julie; Metens, Thierry; Mavroudakis, Nicolas; Guisset, François; Van Vlierberghe, Eline; Smeets, Dirk; David, Philippe; Maertens, Anke; Van Hecke, Wim
Abstract: Introduction: There is emerging evidence that brain atrophy is a part of the pathophysiology of Multiple Sclerosis (MS) and correlates with several clinical outcomes of the disease, both physical and cognitive. Consequently, brain atrophy is becoming an important parameter in patients' follow‐up. Since in clinical practice both 1.5Tesla (T) and 3T magnetic resonance imaging (MRI) systems are used for MS patients follow‐up, questions arise regarding compatibility and a possible need for standardization. Methods: Therefore, in this study 18 MS patients were scanned on the same day on a 1.5T and a 3T scanner. For each scanner, a 3D T1 and a 3D FLAIR were acquired. As no atrophy is expected within 1 day, these datasets can be used to evaluate the median percentage error of the brain volume measurement for gray matter (GM) volume and parenchymal volume (PV) between 1.5T and 3T scanners. The results are obtained with MSmetrix, which is developed especially for use in the MS clinical care path, and compared to Siena (FSL), a widely used software for research purposes. Results: The MSmetrix median percentage error of the brain volume measurement between a 1.5T and a 3T scanner is 0.52% for GM and 0.35% for PV. For Siena this error equals 2.99%. When data of the same scanner are compared, the error is in the order of 0.06–0.08% for both MSmetrix and Siena. Conclusions: MSmetrix appears robust on both the 1.5T and 3T systems and the measurement error becomes an order of magnitude higher between scanners with different field strength. Abstract : Brain atrophy tends to become an important parameter in Multiple Sclerosis patients' follow‐up. Since in clinical practice both 1.5Tesla (T) and 3T magnetic resonance imaging (MRI) systems are used for MS patients follow‐up, questions arise regarding compatibility and a possible need for standardization. Therefore, in this study, brain volume measurements at 1.5T and 3T MRI are evaluated. Our results demonstrate that a small brain atrophy measurement error can be achieved, especially when data of the same scanner are compared, in the order of 0.06–0.08% for both MSmetrix and SIENA.